Adaptive event-triggered control of discrete-time networked systems against randomly occurring infinite distributed delays, random packet losses and sensor saturation. Issue 11 (18th August 2019) - Zhang, He; Zhu, Jianfeng; Lu, Junwei; Wei, Yunliang; Chu, Yuming
Abstract : The saturation input control problem of discrete-time networked systems via adaptive event-triggered communication scheme is discussed in this paper. The criteria are derived by utilising a new Lyapunov functional to guarantee that the considered networked system with randomly occurring infinite distributed delays, random packet losses and sensor saturation is exponentially stable in mean square sense. A novel adaptive event-triggered law is proposed, which is dependent on the exponentially stable index α . The effectiveness of our proposed method is illustrated by both theoretical analysis and numerical simulations.